A Method for Developing Library Collections Based on Intensity Indicators. Issue 4 (2nd October 2018) - Halevi, Gali; Sugrim, Sonali; Gizzi, Chelsea
Abstract: This article reports on a multi-dimensional model to collection development and licensing applied in our library following a major separation from a joint-licensing venture with another institution. Our model includes the use of several core metrics, including usage and the context in which usage is measured. The model includes three metrics; Research Intensity (RI), Educational Intensity (EI) and Clinical Intensity (CI). These metrics take into account the differences between research and non-research departments, and their disciplinary foci. This model can be used in its entirety or can be customized by selecting the metrics that fits the needs of the library.